Pengaruh Budaya Organisasi dan Lingkungan Kerja Terhadap Komitmen Organisasi : Studi Kasus pada PT Laris Mandiri Pratama - Dewi Ariefahnoor; Junaidi Junaidi; Edy Mahfuz; Abdul Kadir. MS (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
In achieving targets, a company cannot be separated from organizational culture, where a company has rules as a differentiator from other companies, the difference is what becomes a characteristic in the company and the different characteristics are called organizational culture. According to Stoner et al (in Fauzi et al 2016:4) organizational culture is a combination of patterns of several basic assumptions, behaviors, stories, and also other ideas. While organizational culture is a very important appreciation such as values, beliefs, and ethics formed by a group that is shared by all members of the organization. This study aims to test: (1) organizational culture influences organizational commitment at PT. Laris Mandiri Pratama, (2) the work environment influences organizational commitment at PT. Laris Mandiri Pratama and (3) organizational culture and work environment influence organizational commitment at PT. Laris Mandiri Pratama. The design of this study is quantitative research and is a survey study. The research population is all employees of PT. Laris Mandiri Pratama and a sample of 38 respondents with Multiple Linear Regression data analysis. Based on the results of the T-Test (Partial Test), partially the Organizational Culture variable (X1) from t count 2.088 > t table 1.659 shows that organizational culture has a significant effect on organizational commitment, partially the Work Environment variable (X2) from t count 3.197 > t table 1.659 shows that the work environment has a significant effect on organizational commitment. While the F-test (Simultaneous Test) F count 29.976 > F table 3.27 proves that organizational culture and work environment significantly affect organizational commitment.